2011
DOI: 10.1242/jcs.076794
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate regulates matrix metalloproteinase-9 expression and breast cell invasion through S1P3–Gαq coupling

Abstract: SummaryRecent evidence suggests that inflammation is involved in malignant progression of breast cancer. Sphingosine 1-phosphate (S1P), acting on the G-protein-coupled receptors, is known as a potent inflammatory mediator. In this study, the effect of the inflammatory lipid S1P on the regulation of invasive/migratory phenotypes of MCF10A human breast epithelial cells was investigated to elucidate a causal relationship between inflammation and the control of invasiveness of breast cells. We show that S1P causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 80 publications
5
92
2
Order By: Relevance
“…SPHK1 is an enzyme responsible for S1P production and is involved in many cellular processes, such as promoting cellular proliferation and stimulating cell survival and metastasis 2, 3, 4. SPHK1 mainly express in the cytosol and needed to be translocated to the membrane while be activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPHK1 is an enzyme responsible for S1P production and is involved in many cellular processes, such as promoting cellular proliferation and stimulating cell survival and metastasis 2, 3, 4. SPHK1 mainly express in the cytosol and needed to be translocated to the membrane while be activated.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine‐1‐phosphate (S1P) is a bioactive sphingolipid metabolite involved in many pathophysiological processes 1, 2, 3, 4. The intracellular level of S1P as a secondary messenger 5 is regulated by several enzymes including anabolism and catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, S1P/ S1P 2 signaling was shown to stimulate Rac GTPase-activating protein (Rac-GAP) and thus abrogate growth factor-induced Rac activation and chemotaxis (25,60). S1P/S1P 3 -mediated chemotactic response was shown to play important roles in various physiological and pathophysiological responses (30,(33)(34)(35)(36)(37)(38). However, molecular details of the S1P 3 -mediated chemotactic response are poorly understood and remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular details of the S1P 3 -mediated chemotactic response are poorly understood and remain to be elucidated. S1P/S1P 3 -mediated chemotaxis was shown to play important roles in the invasion/migration phenotype of MCF10A human breast epithelial cells (33), prostate migration of carcinoma cells (30), B-cell development, egress and positioning within the bone marrow (34), homing of bone marrow-derived cells (35), dissemination of inflamed dendritic cells (36), shuttle of B cells from splenic follicular areas to marginal zone (37), and high density lipoprotein-stimulated endothelial cell migration (38), among others. We recently showed that S1P 3 receptors are abundantly expressed in a panel of human lung adenocarcinoma cell lines, and S1P 3 signaling plays an essential role in stimulating the migration/invasion of these cell lines (39).…”
mentioning
confidence: 99%
“…The S1P 2 and S1P 3 receptors could couple with the G i , G q and G 12/13 proteins to inhibit cell migration via ρ signaling (41,45). S1P modulates the levels of MMPs, such as MMP-2 and MMP-9, regulating cell invasion (46)(47)(48). Recent findings have suggested that EMT-associated MMPs are involved Figure 1.…”
Section: S1p-induced Em T Can Be Snail-mmps Signalingmentioning
confidence: 99%